2014
DOI: 10.1111/pbaf.12037
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of State Government Debt‐Related Derivatives Policies

Abstract: The increasing use of debt‐related derivatives over the last 10 years, combined with the recent global financial crisis' impact on these instruments, greatly affected the finances of many state and local governments in the United States. Some observers believe the negative effects could have been minimized had governments established prudent financial risk management policies governing these products. This research describes and analyzes debt‐related derivatives policies at the state level. It finds that while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…One might suggest that more guidance for financial managers on how and when to use swaps and derivatives is needed. Policies governing the use of debt-related derivatives are limited in their depth of coverage at the state level (Singla and Luby 2014); it seems unlikely that policy guidance in cities would be stronger. This is one area where things can be improved, as more detailed swaps policies discussing the process by which transactions ought to be evaluated and the acceptable risk–reward tradeoff would make decisions less susceptible to underwriter or financial institution influence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One might suggest that more guidance for financial managers on how and when to use swaps and derivatives is needed. Policies governing the use of debt-related derivatives are limited in their depth of coverage at the state level (Singla and Luby 2014); it seems unlikely that policy guidance in cities would be stronger. This is one area where things can be improved, as more detailed swaps policies discussing the process by which transactions ought to be evaluated and the acceptable risk–reward tradeoff would make decisions less susceptible to underwriter or financial institution influence.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, with reward comes risk, and there are numerous risks associated with these deals, the most prominent of which are basis risk and termination risk (Singla and Luby 2014). Basis risk is the chance that the two floating payments do not net out to zero.…”
Section: Background: the Mechanics Of Debt-related Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated the use of derivatives in federal countries, especially those adopting the International Public Sector Accounting Standards (IPSAS) such as Brailsford et al (2005); Stewart and Cox (2008); Howell-Moroney and Hall (2011); Luby (2012); Denison and Gibson (2013); Luby and Singla (2014); and Khumawala et al (2016). A detailed description of purpose, mechanism and risks of swaps in the public sector is that by Luby and Kravchuk (2013) (pp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…the GASB statement n. 53 effective since 2008). Most authors underlined the absence of policies and standardised rules on the trading, management and accounting of such complex contracts by local administrations that can explain these losses (Luby and Kravchuk, ; Singla and Luby, ). Among the others, (Khumawala et al., ) empirically investigated the use of OTC contracts by 300 US municipalities and found that interest rate swaps are the most popular contracts, and that large and more sophisticated municipalities are more likely to engage in such contracts, together with small ones if managed by unsophisticated managers.…”
Section: Literature Reviewmentioning
confidence: 99%